Comparación de modelos matemáticos : una aplicación en la evaluación de alimentos para animales (2007)
ABSTRACT: The digestibility and degradation rates of food can be estimated through the in vitro gas production technique. The gas curves generated can be described by diverse mathematical models (exponential, logistic, and empirical). The objective of this work was to present some mathematical models commonly used to describe gas production curves and to review some statistical tools useful to evaluate their adjustment capacity. Two models, either a logistic or an empirical proposed by Schofield et al, and France et al, respectively, were used to fit the profiles of gas production of six forage species. The selected criteria for evaluation of their adjustment capacity were: 1) square means error (CME), 2) Akaike (AIC) or 3) Bayesian(BIC) information criteria, 4) coefficient of determination (R2), 5) residual analysis, and 6) Durban-Watson dosim (DW). The best models for evaluation of gas production are those that present the best balance between data adjustment capacity and biological coherence, being necessary their evaluation under the most varied experimental conditions, in order to choose the best model for each specific situation.